1996
DOI: 10.1021/ma960756b
|View full text |Cite
|
Sign up to set email alerts
|

Does Quantum Mechanical Tunneling Affect the Validity of Hole Volume Distributions Obtained from Positron Annihilation Lifetime Measurements?

Abstract: Positron annihilation lifetime spectroscopy, which is applied to measure distributions of hole volume sizes in polymers, uses a model to relate the positronium (Ps) lifetime to hole volume dimensions. It is assumed in this model that the Ps remains in one site until annihilation. Recently, the validity of this last assumption has been questioned by Yu et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…This assumption is confirmed by calculations which showed that the Ps will exist in the hole where it is formed or first trapped until annihilation (Anderson localization) [37,38]. That means that the o-Ps lifetime mirrors the hole size at the moment of annihilation and in that way the fluctuating free volume of a liquid [27,28,31].…”
Section: Introductionmentioning
confidence: 71%
“…This assumption is confirmed by calculations which showed that the Ps will exist in the hole where it is formed or first trapped until annihilation (Anderson localization) [37,38]. That means that the o-Ps lifetime mirrors the hole size at the moment of annihilation and in that way the fluctuating free volume of a liquid [27,28,31].…”
Section: Introductionmentioning
confidence: 71%
“…A hot Ps interacting with the lattice can easily emit phonons producing variations of on-site energy δV associated with vibration of the box. If δV /BW >> 1 (where BW is the bandwidth) Ps localizes [30]. Only when Ps has dissipated all its energy to emit phonons such as δV > BW its migration can be wavelike (in our case BW ≃ 0.2 eV for the lowest band).…”
mentioning
confidence: 88%
“…The process of quantum confinement is advantageous for such experiments because tunneling Ps becomes localized in a subset of the pore structure, and the effective density of Ps is increased [290]. Similarly, tunneling rates between different accessible pores may have to be taken into account in porosity measurements using lifetime measurements [291,292]. One may also study Ps-gas interactions within such structures via annihilation radiation [293][294][295], including aerogels [296][297][298], and using laser spectroscopy it is also possible to study the effects of Ps confinement directly [115].…”
Section: Ps Productionmentioning
confidence: 99%